BIOGRAPHY OF ABDURRAHMAN SAYOETI THOUGHT (1965 – 1999) - Wiji Nur Asih, Abd. Rahman (Universitas Batanghari Jambi, 2017)
Abstrac This study aims to provide an overview of the biography of Abdurrahman Sayoeti thought (1965-1999). The research method used is historical method, which is a process of testing and critically analyzing past events, with stages starting from heuristics, criticism, interpretation, historiography. The results of various important positions have been held by Abdurrahman Sayoeti, first became director of APDN in 1965, through the leadership of Abdurrahman Sayoeti, has given birth to quite a lot of graduates and has the leadership seeds to build Jambi area, secondly, as Sekwilda Level I Jambi up to two periods (1969), Abdurrahman Sayoeti's career was so developed that it was given the confidence to develop regional tasks accompanying Governor Macshun Syofwan, as Deputy Governor of KDH Level I Jambi one period (1985). Finally in the peak of his career through elections conducted by representatives of the people in the Jambi Provincial Legislative and with full support by the people so as to make Abdurrahman Sayoeti as Governor of Jambi for two periods, from 1989 to 1999. The results of career into Governor of Jambi Province, Abdurrahman Sayoeti giving a lot of many change to build Jambi area.Keywords : Biography, Abdurrahman Sayoeti Thought